ALAM SUMBER KEHIDUPAN: MELIRIK KEHIDUPAN MASYARAKAT PETUK KATIMPUN DI PINGGIRAN SUNGAI RUNGAN - Muhammad Zusanri Batubara; Novia Rahmah; Wahyu Simbolon; Tata Agustina; Hasanuddin Hasanuddin (SEIKAT: Jurnal Ilmu Sosial, Politik dan Hukum, 2023)
Petuk Katimpun is a village in Palangka Raya City which is located on the banks of the Rungan River. The activities of the Petuk Katimpun community are dominantly in direct contact with the Rungan river. The Rungan River is one of the dominant sources of livelihood for the community. Various livelihoods of the Petuk Katimpun community such as fishermen and gold miners are sourced from the Rungan river. This research aims to find out how the life of the Petuk Katimpun community on the banks of the Rungan river is viewed from various aspects such as economy, education and health. The research method used is qualitative research with a descriptive approach. The data collection techniques used in this research are observation, interview, documentation study, and literature study. The informants in this research are the head of the family and housewives who live on the riverbanks. The results of this study show that most of the people of Petuk Katimpun depend on their livelihoods as fishermen. The community around the river develops small businesses such as opening kiosks to sell fishery products. Maintaining the environment around the river is very important for the fishing community because a clean and healthy environment can affect the catch of fish and other natural resources. The biggest challenge faced by the Petuk Katimpun community in preserving the Rungan River is environmental damage carried out by irresponsible individuals, including gold miners.